NUMERICAL METHOD FOR SOLUTION OF FOURTH-ORDER VOLTERRA INTEGRO-DIFFERENTIAL EQUATIONS BY GREEN'S FUNCTION - Akgun, Fatma a.; Rasulov, Zaur (UNIV KRAGUJEVAC, FAC SCIENCE, 2025)
In this paper, we generalize Picard-Green's Embedded method for solving fourth-order Volterra integro-differential equations. We prove the existence and uniqueness theorems. Moreover, we illustrate some numerical examples to present the better approximation with a minimum error. We use MATLAB for numerical solutions.
Keywords: Fixed point iteration; Picard-Green's method; convergence rate; numerical approximation; WAVELET-GALERKIN METHOD; DIFFERENTIAL-EQUATIONS; ITERATION METHOD; Mathematics